STEEL DOME PROJECT DESIGN BOGOR CONVENTION CENTER OPTIMIZATION FOR BUDGET AND AESTHETIC ARCHITECTURE - Hamonangan Girsang; Cecep Indra Lesmana (NAROTAMA UNIVERSITY, Indonesia, 2020)
A building needs to be considered various aspects to meet the values - both economic value, cost, durability, impact on the environment to aesthetics or beauty. This research was conducted to make a comparison of the Bogor Convention Center project which was built using the Dome structure with the WF Steel Profile which will be replaced by using steel pipe material. The software used in designing steel is SAP2000 Analysis. SAP2000 is a 3D modeling application that is able to design steel structures that produce analysis and calculation results include static analysis, finite element dynamics analysis, as well as images, reports or other outputs from one structural model. As for the depiction using Autocad where Autocad functions to detail the connections that are in the dome frame of the study. Analysis and Design of a spherical dome structure with building functions as a convention center. The structure of the shell is used as the roof of the building so that the aesthetic elements and values of the architecture of the shell structure can be seen its beauty from the inside of the building. The analysis conducted is an analysis of the internal forces and design of reinforcement in the structure.